2014
DOI: 10.1021/cs401199f
|View full text |Cite
|
Sign up to set email alerts
|

A Series of NiM (M = Ru, Rh, and Pd) Bimetallic Catalysts for Effective Lignin Hydrogenolysis in Water

Abstract: In this paper, NiRu, NiRh, and NiPd catalysts were synthesized and evaluated in the hydrogenolysis of lignin C− O bonds, which is proved to be superior over single-component catalysts. The optimized NiRu catalyst contains 85% Ni and 15% Ru, composed of Ni surface-enriched, Ru−Ni atomically mixed, ultrasmall nanoparticles. The Ni 85 Ru 15 catalyst showed high activity under low temperature (100 °C), low H 2 pressure (1 bar) in β-O-4 type C−O bond hydrogenolysis. It also exhibited significantly higher activity o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
284
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 444 publications
(293 citation statements)
references
References 63 publications
8
284
1
Order By: Relevance
“…It was proposed that the improved yield from combining Raney Ni with a zeolite arose from the latter hindering the reaction between the parent lignin and other more reactive lignin fragments that could together to produce high molecular weight oligomers. Bimetallic NiM (M = Ru, Rh, Pd, Au, Mo) catalysts have also been studied for lignin hydrogenolysis [33,34], [35] [36], wherein NaOH addition proved beneficial, promoting the formation of aromatic compounds and supressing arene hydrogenation. Konnerth et al [37] also observed increased Organosolv lignin depolymerization via NaOH addition to the aqueous reaction mixture containing an Ni 7 Au 3 Fig.…”
Section: Hydrogenolysismentioning
confidence: 99%
“…It was proposed that the improved yield from combining Raney Ni with a zeolite arose from the latter hindering the reaction between the parent lignin and other more reactive lignin fragments that could together to produce high molecular weight oligomers. Bimetallic NiM (M = Ru, Rh, Pd, Au, Mo) catalysts have also been studied for lignin hydrogenolysis [33,34], [35] [36], wherein NaOH addition proved beneficial, promoting the formation of aromatic compounds and supressing arene hydrogenation. Konnerth et al [37] also observed increased Organosolv lignin depolymerization via NaOH addition to the aqueous reaction mixture containing an Ni 7 Au 3 Fig.…”
Section: Hydrogenolysismentioning
confidence: 99%
“…A key advantage of our lignin depolymerization method is the retention of functional groups in the major phenolic product 8, as these groups are frequently lost in other lignin depolymerization processes. [13,17] Future studies will focus on integrating methods to recover and recycle both the organic solvents used and the solubilized zinc salts in the aqueous waste stream. The environmental and cost implications of using a halogenated organic catalyst, such as DDQ, will also be assessed.…”
Section: Technologiestoproducechemicalsandfuelsfromrenewablementioning
confidence: 99%
“…Then a sample was acquired from the organic phase for GC-MS analysis. For GC-MS analysis, the response factor for each product was standardized with the use of efficient carbon number (Scanion and Willis, 1985;Zhang et al, 2014b), which enabled the analysis of compounds without pure standards.…”
Section: Lignin Depolymerization In a Parr Reactormentioning
confidence: 99%